2017
DOI: 10.7326/m16-1256
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and Access for Americans With Chronic Disease Under the Affordable Care Act

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 22 publications
1
61
0
Order By: Relevance
“…We confirm (results are in appendix) findings from previous studies [1316] that nationwide, blacks and Hispanics were less likely to have insurance coverage in the pre-ACA period than non-Hispanic whites were. However, compared to non-Hispanic whites, they also made larger gains in coverage post-ACA.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…We confirm (results are in appendix) findings from previous studies [1316] that nationwide, blacks and Hispanics were less likely to have insurance coverage in the pre-ACA period than non-Hispanic whites were. However, compared to non-Hispanic whites, they also made larger gains in coverage post-ACA.…”
Section: Resultssupporting
confidence: 88%
“…States that elected to expand Medicaid covered all adults up to 133% of Federal Poverty Limit (FPL). That these provisions expanded insurance coverage is evidenced by several studies using datasets such as Gallup-Healthways Wellbeing Index [2, 12], the National Health Interview Survey [14], the American Community Survey [3], the Commonwealth Fund Survey [22] and BRFSS [5, 13, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Previous work has indicated that the young adult expansion of employer-sponsored insurance resulted in increases in coverage among cancer survivors aged 19 to 25 years, 18 including greater access to health care through an earlier stage of disease at diagnosis. 12 Medicaid expansion has increased coverage and access to care among lowincome adults, 19,20 and has been associated with increased insurance rates among newly diagnosed patients with cancer. 21 Although Medicaid expansion has the potential to affect affordability and access to medical care among lowincome cancer survivors, 3 to the best of our knowledge the effect on physician access and affordability of care among cancer survivors has not yet been investigated.…”
Section: Althoughmentioning
confidence: 99%
“…Finally, individuals with chronic conditions are most likely to benefit from insurance expansion because they require ongoing treatment and management and are more sensitive to high levels of cost-sharing. 15,16 Stratifying analyses by chronic condition status can focus on meaningful health improvements among the population most likely to benefit. Moreover, chronic conditions are more prevalent among childless adults than other adults who gained coverage through the Affordable Care Act.…”
Section: Introductionmentioning
confidence: 99%